2009
DOI: 10.1080/00207540903104210
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the capture of manufacture best practice in product lifecycle management

Abstract: Abstract:The capture of manufacturing best practice knowledge in product lifecycle management systems has significant potential to improve the quality of design decisions and minimise manufacturing problems during new product development. It should both support manufacturing engineers and offer designers an improved ability to understand the manufacturing consequences of alternative design options. However, providing a re-useable source of manufacturing best practice is difficult due to the complexity of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…There is no widely adopted approach or standard for ontology development, and there is lack of practical ontology methods for supporting the engineering design process (Darlington and Culley 2008;Lim, Liu, and Lee 2011). The literature has identified that many of the ontology development attempts in product design are commonly technology oriented (Kim, Manley, and Yang 2006;Gunendran and Young 2009;Bock et al 2010;Chungoora and Young 2010;Panetto, Dassisti, and Tursi 2012). There is lack of research projects focused on bridging the gap between ontology-based frameworks and engineering design activities.…”
Section: Related Work and Research Scopementioning
confidence: 99%
“…There is no widely adopted approach or standard for ontology development, and there is lack of practical ontology methods for supporting the engineering design process (Darlington and Culley 2008;Lim, Liu, and Lee 2011). The literature has identified that many of the ontology development attempts in product design are commonly technology oriented (Kim, Manley, and Yang 2006;Gunendran and Young 2009;Bock et al 2010;Chungoora and Young 2010;Panetto, Dassisti, and Tursi 2012). There is lack of research projects focused on bridging the gap between ontology-based frameworks and engineering design activities.…”
Section: Related Work and Research Scopementioning
confidence: 99%
“…design viewpoints and manufacturing viewpoints. Three good examples of this are Fenves et al (2005), Gunendran and Young (2010) and Chungoora et al (2013). Relationships between a design feature and a design function or design part family are explored by Chungoora et al (2013).…”
Section: Feature Knowledge Relationship Structurementioning
confidence: 99%
“…Over the past few years there has been an emphasis placed upon the study and development of knowledge based systems to enable better knowledge management and reuse of that knowledge within manufacturing environments (Cochrane et al 2009;Gunendran and Young 2010;Chungoora et al 2013). There are some drawbacks to these approaches in that they can consume inordinate amounts of time to create a knowledge base and test it before they are even implemented within a commercial environment (Mohammed, May and Alavi 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagram identifies general categories of information, the core types of concepts (i.e., classes) that fall within these categories and important associations (i.e., relations) across concepts. The fundamentals of this ontology involve the notion of part planning using part families and features [32,33], where sufficient flexibility in the formal meaning of concepts has been accommodated to support the improved configuration of design and manufacturing solution.…”
Section: Building Blocks Of the Imks Approachmentioning
confidence: 99%